Meet the Joneses: An Empirical Investigation of Reference Groups in Relative Income Position Comparisons - Markus Schaffner; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2008)
It is generally understood that people care about their absolute income position, and several studies have in fact moved beyond this, showing that people also place considerable signifcance on their relative income position. However, empirical evidence about the behavioural consequences is scarce. We address this shortcoming by exploring the relative income effect in a (controlled) sporting contest environment. Specifically, we look at the pay-performance relationship by working with a large panel data set consisting of 26 NBA seasons. We explore how closeness affects positional concerns exploring in detail several potential reference groups. This allows checking of their relevance and of the scope of comparisons, a critical aspect in the literature that requires further investigation.
Keywords: 330